2011
DOI: 10.4103/0019-5049.84841
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as an intrathecal adjuvant for postoperative analgesia

Abstract: Background:Spinal anaesthesia is the most common approach which is used for lower limb surgery. Dexmedetomidine is the recent drug which acts on α2-adrenergic receptors in the dorsal horn of the spinal cord to produce analgesic effects.Aim:Efficacy and safety of intrathecal dexmedetomidine added to ropivacaine.Setting and Design:Randomised double blind trial.Methods:Sixty patients were randomly allocated to receive intrathecally either 3 ml of 0.75% isobaric ropivacaine + 0.5 ml normal saline (Group R) or 3 ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
79
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 16 publications
13
79
0
2
Order By: Relevance
“…Similar findings are observed by Mahendru et al .,[18] Gupta et al .,[19] and Al-Mustafa et al . [20] The quality of surgical anesthesia was excellent in both groups in the intraoperative period.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings are observed by Mahendru et al .,[18] Gupta et al .,[19] and Al-Mustafa et al . [20] The quality of surgical anesthesia was excellent in both groups in the intraoperative period.…”
Section: Discussionsupporting
confidence: 92%
“…Although dexmedetomidine has been approved by the Food and Drug Administration as a sedative for mechanically-ventilated adult intensive care unit patients, it has not been approved for intrathecal use. However, dexmedetomidine used in neuraxial blocks in experimental and clinical studies without neurological deficits has encouraged the use of dexmedetomidine by the intrathecal route with levobupivacaine (2,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). To the best of our knowledge, this combination has not been used previously by the intrathecal route in humans, which shows the importance of this study.…”
Section: Discussionmentioning
confidence: 92%
“…Fifteen of the included trials reported on the effectiveness of dexmedetomidine on the prevention of perioperative shivering compared with placebo, 11 studies [22–30, 44, 45] administered via spinal route, and 4[36–39] researches via epidural route. Patients investigated in 5 trials [25, 38, 39, 44, 45] were nearly full term parturients selected for cesarean section.…”
Section: Resultsmentioning
confidence: 99%